Can Cardiothymic Thoracic Ratio be a Marker of Mortality in Preterm Neonates with Respiratory Distress Syndrome? - Ram Narain Sehra; Mahendra Kumar Palsania; Chandan Verma; Suniti Verma (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Thymic size is measured as Cardiothymic: Thoracic ratio (CT/T ratio) in chest X-ray. In a state of stress, the thymus tissue rapidly involutes, owing principally to the thymocytolytic effect of glucocorticosteroids. Different pre and postnatal factors affect thymic size in neonates. Aim: To determine the thymic size in preterm neonates with Respiratory Distress Syndrome (RDF), its relation to survival to determine which antenatal and postnatal factors influence thymic size. Materials and Methods: This prospective observational study was carried out in neonatal units of tertiary care hospital in North India from May 2018 to September 2019. Premature (<37 weeks gestation) neonates admitted in NICU with clinical and radiological evidence of RDS were included in the study. CT/T ratio was measured in chest X-ray. The quantitative data was presented as mean and standard deviation (SD) and were compared using student t-test, one-way ANOVA test and continuous non parametric data were compared using Pearson correlation coefficient test. Results: Mean age of 110 studied neonates was 32.07±1.76 weeks. The mean±SD CT/T in the study was 0.361±0.043. Mean CT/T ratio (0.372±0.043) of non survivor (44) was higher (0.356±0.043) than survivor neonates (66). This difference was statistically not significant (p-value=0.058). Mean CT/T ratio >0.361 has sensitivity 59.09% and specificity 68.18% for non survivor group. Logical regression analysis for probability of survival showed that as CT/T ratio increases probability of survival decreases. Mean CT/T ratio was not affected by gestational age, sex, mode of delivery, use of antenatal steroid, pre-eclampsia, mother's parity, perinatal asphyxia and sepsis. Conclusion: The mean CT/T ratio was higher in non surviving neonates with RDS as compared to those who survived. Mean CT/T ratio is a poor predictor for mortality in premature neonates with RDS.